Diachronic study of vegetation cover change using remote sensing in Ain Skhouna (Saida) from 1991 to 2021 - Boukacem, Abdelkader; Benaissa , Noureddine; Belkhoudja, Moulay; Kharoubi, Omar (Journal of Degraded and Mining Lands Management, 2026)
To evaluate the spatiotemporal dynamics of vegetation in semi-arid conditions, a diachronic analysis of plant cover change in the municipality of Ain Skhouna (Saida Province) between 1991 and 2021 was conducted. Landsat satellite imagery (TM and ETM+) was used to compute the Normalized Difference Vegetation Index (NDVI) to quantify vegetation cover dynamics over three decades. The data were processed using ENVI 5.3 and ArcGIS 10 software, and the results were compared using supervised classification and change analysis, supplemented by field observations to validate the results. The results of this study revealed marked spatio-temporal variations in vegetation cover, with a substantial decline in vegetation density between 1991 and 2000. This degradation can be attributed to multiple factors, including prolonged drought, anthropogenic pressure, overgrazing, and increased soil salinity. However, the classification maps indicated a gradual recovery of vegetation cover from 2000 to 2021, which can be associated with more favorable climatic conditions and the implementation of localized reforestation initiatives. These results highlight the importance of diachronic monitoring of vegetation cover for the conservation of plant biodiversity and the sustainable management of Sahelian–steppe ecosystems. The study emphasizes the need to integrate remote sensing tools into ecological monitoring programs to guide restoration strategies and support adaptation to climate change in steppe regions.